A Synergistic Assessment of Bio-kinetics and Life Cycle Environmental Impacts of Different Agricultural Biomass Sources in Turkey - Yetilmezsoy, Kaan; Cetinkaya, Afsin Yusuf; Bilgili, Levent (SPRINGER, 2022)
This study was conducted to explore the biochemical methane potential of three different agricultural biomass sources including sunflower (Helianthus annuus L.) meal, Jerusalem artichoke (Helianthus tuberosus L.), and food waste (mixture of cooked and uncooked food) under the identical mesophilic biodegradation conditions. A synergistic quantitative analysis was explicitly introduced to appraise the biochemical methane potentials and life cycle environmental impacts (in terms of greenhouse gases and various midpoint categories) of these agro-industrial wastes. Three different sigmoidal microbial growth curve models (modified Gompertz equation, transference function (reaction curve-type model), and logistic function) were also implemented to determine the bio-kinetics of the studied substrates using a novel MATLAB (R)-based hybrid optimization procedure. The experimental results indicated that the ultimate methane yield (915 mL CH4/g VS) achieved for the canteen-originated food waste was 1.46 and 1.37 times higher than the yields obtained from Jerusalem artichoke and sunflower meal, respectively. The logistic function simulated by a Quasi-Newton cubic line search algorithm best described the bio-kinetics of all agro-industrial substrates with the minimum nonlinear iterations and function counts. According to the life cycle assessment, the use of Jerusalem artichoke in biogas production showed the worst performance in environmental terms. However, no obvious difference was found between the use of food waste and sunflower meal.
Keywords: Agricultural biomass; Biochemical methane potential; Computational programming; Life cycle assessment; Kinetic modeling; ANAEROBIC CO-DIGESTION; ENHANCED METHANE PRODUCTION; MILL WASTE-WATER; FOOD WASTE; JERUSALEM-ARTICHOKE; PRETREATMENT; SLUDGE; STRAW; BMP; FEEDSTOCKS; Environmental Sciences & Ecology